Philosophy of Aristotle - "Allan, D.J." (London, 1952)
The author's purpose is to outline Aristotle's principal doctrines with reference to the circumstances in which they were formed and to show that it is still worth while to read Aristotle, as well as Plato. To ease the path for those who approach the philosopher without a classical training, the opening chapter gives a summary account of the form if Aristotle's writings and the growth of his philosophy. Mr Allan's book should reassure those who have been inclined to avoid Aristotle as 'too difficult', and lead them to share the enthusiasm of critics so well qualified and so far apart as Cicero and Somerset Maugham, who praised Aristotle's style.
Keywords: Philosophy